2002
DOI: 10.1034/j.1600-0447.106.s412.25.x
|View full text |Cite
|
Sign up to set email alerts
|

Perception of aggression, personality disorders and psychiatric morbidity in nursing students

Abstract: Objective:  To determine the relationship between perception of aggression, personality disorders and psychiatric morbidity. Method:  Ninety nursing students were interviewed. A two‐stage transversal analysis was used, the first stage using the Spanish version of the general health questionnaire (GHQ‐28), the true‐false test of international personality disorders (IPDE) of Loranger, and the perception of aggression scale (POAS) of Jansen. For the second stage we used the Spanish version of the clinical intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 6 publications
6
20
0
Order By: Relevance
“…Muro et al . () revealed similar results to those of this study by reporting that the scores of student nurses on the POAS showed the impact of sex differences. However, Palmstierna and Barredal () found the opposite, in which male nurses with more experience were more likely to perceive aggression as unacceptable.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Muro et al . () revealed similar results to those of this study by reporting that the scores of student nurses on the POAS showed the impact of sex differences. However, Palmstierna and Barredal () found the opposite, in which male nurses with more experience were more likely to perceive aggression as unacceptable.…”
Section: Discussionsupporting
confidence: 87%
“…Overall, aggression was perceived to be an unacceptable mode of behavior by the nursing students. This finding is consistent with those of previous studies investigating nurses or nursing students' perceptions of aggression (Abderhalden et al ., ; Muro et al ., ; Bowers et al ., ; Pazvantoglu et al ., ). However, participants in previous studies viewed patient aggression to be a relatively normal behavior (Finnema et al ., ; Abderhalden et al ., ; Palmstierna & Barredal, ; De Benedictis et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…to measure the attitude of 90 nursing students in Spain. The study demonstrated high agreement with the Dutch results regarding aggression as a violent and as a normal reaction, but low agreement regarding aggression as a functional reaction (Muro et al . 2002).…”
Section: Introductionsupporting
confidence: 77%
“…2002). The authors found no significant relationships between the student nurses’ attitudes to aggression and their respective scores on the ‘General Health Questionnaire’ and the ‘International Personality Disorder Examination’ but a significantly higher proportion of males perceiving aggression as a violent reaction (Muro et al . 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It seems plausible that both factors will be related in some way to evaluations of containment methods by nurses, with perhaps nurses who express more understanding of aggressive behaviour being less willing to use strongly coercive containment methods. A previous study has shown a gender difference in POAS scores in nursing students, with female students more likely to consider aggression unacceptable (Muro et al 2002). That same study showed no relationship between personality disorder in the nursing students and POAS scores.…”
Section: Introductionmentioning
confidence: 80%